Spanish translation of the mood rhythm instrument: a novel approach to mood evaluation - Francisco, Ana Paula; Oliveira, Melissa Alves Braga de; Carissimi, Alicia; Fabris, Raul Costa; Ilgenfritz, Carlos Augusto Vieira; Souza, Camila Morelatto de; Medeiros, Madeleine Scop; Adan, Ana; Hidalgo, Maria Paz Loayza (Clinical and Biomedical Research, 2017)
Introduction: The Mood Rhythm Instrument (MRI) is a questionnaire developed to assess the circadian rhythm of mood-related behaviors. The aim of this study was to translate this instrument from Brazilian Portuguese into Spanish. Methods: The translation process consisted of forward translation, adjustment, back translation, back translation review and harmonization. Results: Comparing the initial Spanish translation and the final Spanish version, there were no semantic differences and the items were not changed. Conclusions: The Spanish version of the MRI is ready to be tested in a Spanish population. In the future, assessing and comparing mood-related behaviors in transcultural studies will be possible. Keywords: Circadian rhythms; daily rhythms; mood; psychometric; chronobiology.